Gut microbiota and urinary tract infections in children - L. A. Levanova; A. A. Markovskaya; L. Yu. Otdushkina; Yu. V. Zakharova (Фундаментальная и клиническая медицина)
Aim. To evaluate the role of intestinal dysbiosis in the development of urinary tract infections in children admitted to a multidisciplinary hospital.Materials and Methods. We performed a bacteriological analysis of 2,694 urine samples collected from ≤ 3-years-old children who have been admitted to a multidisciplinary hospital (Kemerovo, Russian Federation). Urine specimens were inoculated by the 4-sector technique. Concurrently, we quantified the intestinal microbiota and its antimicrobial resistance in 100 children with urinary tract infections.Results. Titers of pathogenic microbes significantly differed in patients from distinct units (p = 0.02). The highest number of positive samples was detected in the neonatal pathology and neonatal intensive care units (43.8% each) as well as urology unit (37.9%). The most frequent pathogens belonged to Enterobacteriaceae family, in particular Escherichia coli, Klebsiella spp., Enterobacter spp., and Proteus spp. All studied children (100/100) suffered from intestinal dysbiosis. Titers of Bifidobacterium spp. and Lactobacillus spp. were reduced to 6 (5.0; 8.0) and 5 (4.0; 6.0) lg CFU/g, respectively. In 89.2% children, Escherichia coli lac+ levels were elevated to 9-10 lg CFU/g. Of note, 18.9% children had high Escherichia coli lac- titers [8 (6.0; 9.0) lg] and 24.3% had high Escherichia coli hly+ titers [5 (4.5; 6.0) lg] in the intestine. We have also found a high frequency (44.6%) and density [8.1 (7.0; 8.5) lg] of Klebsiella spp., in the intestinal mucosa of such patients. Notably, Enterobacter spp. and Proteus spp. were abundant [7 (5.0; 8.0) CFU/g] in the intestinal microbiota of 10.8% children. The prevalence of resistance strains in the studied setting reached 63%.Conclusions. More than 75% children with urinary tract infections suffer from intestinal dysbiosis. The microbiome of these patients was predominantly composed of Enterobacteriaceae and was characterized by high titers of Escherichia coli lac+, Klebsiella spp., Enterobacte spp., and Proteus spp. Similar profile of antimicrobial resistance in urinary and intestinal isolates of enterobacteria suggests intestinal microbiome as the main source of pathogens causing urinary tract infections in children.